2017
DOI: 10.3892/etm.2017.4122
|View full text |Cite
|
Sign up to set email alerts
|

Identification a nonsense mutation of APC gene in Chinese patients with familial adenomatous polyposis

Abstract: Abstract. Familial adenomatous polyposis (FAP; Mendelian of Inherintance in Man ID, 175100) is a rare autosomal dominant disorder characterized by the development of numerous adenomatous polyps throughout the colon and rectum associated with an increased risk of colorectal cancer. FAP is at time accompanied with certain extraintestinal manifestations such as congenital hypertrophy of the retinal pigment epithelium, dental disorders and desmoid tumors. It is caused by mutations in the adenomatous polyposis coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Congenital retinal pigment epithelial cell hypertrophy occurs only in patients with mutations between codon 457 and codon 1444 14. Mutations with extra-polyp phenotypes, such as dermatofibroma, osteoma, epidermoid cysts and upper gastrointestinal polyps, were found to be the most common mutations between codons 1445 and 1578 or codons 1395 and 1493 15. In our patient, we found masses of various sizes distributed over the colon and rectum, and malignant lesions were noted in the colon and the rectum.…”
Section: Discussionmentioning
confidence: 47%
“…Congenital retinal pigment epithelial cell hypertrophy occurs only in patients with mutations between codon 457 and codon 1444 14. Mutations with extra-polyp phenotypes, such as dermatofibroma, osteoma, epidermoid cysts and upper gastrointestinal polyps, were found to be the most common mutations between codons 1445 and 1578 or codons 1395 and 1493 15. In our patient, we found masses of various sizes distributed over the colon and rectum, and malignant lesions were noted in the colon and the rectum.…”
Section: Discussionmentioning
confidence: 47%
“…Also, a 5 nucleotide deletion at the hot spot codon 1309 (c.3927_3931delAAAGA) in 15% of the FAP cases is reported to be the most frequent germline mutations 2,28,29 . Many studies have also reported positive correlations between experimental manifestations and APC mutations 30‐32 . Friedl et al, 33 Plawski et al, 34 and Kashfi et al 35 Investigated APC mutations in unrelated FAP patients and found different nucleotide deletions in hot spot codons.…”
Section: Discussionmentioning
confidence: 99%
“…Adenomas at the ampulla of Vater can obstruct bile flow and pancreaticobiliary enzymes, leading to acute pancreatitis. 16 Among the extra colonic alterations, including other types of cancers, gastric and duodenal polyps, desmoids tumors, 17 congenital hypertrophy of the retinal pigment epithelium, 17,21 osteomas, 21 epidermal cysts, 17 and oral abnormalities, 21 which are reported to be present from 58 to 100% of affected individuals. 17 Among these include ST, 2,17,22 appeared in 11-27% of patients, mostly between teeth in the alveolar bone or attached to follicle of an impacted tooth, common sites were anterior and around canines, 2 dentigerous cysts, 22 unerupted teeth, 17,22 congenital absence of one or more teeth, 22 odontomas, 17,22 and osseous jaw lesions.…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%